Effectiveness of resisted training on change-of-direction performance in athletes and active populations: A systematic review with meta-analysis - Zhang, M.; Zhang, X.; Fang, W.; Wu, K.; Bian, J. (Journal of Sports Sciences, 2026)
This systematic review aimed to evaluate the effects of resisted sprint and plyometric training on change-of-direction (CoD) performance across populations ranging from recreationally active adults to athletes. We searched PubMed, Google Scholar, SPORTDiscus, Scopus, and Web of Science up to June 2024, and included 21 randomized controlled trails (30 intervention groups) comparing resisted modalities against active and passive controls. A multilevel random-effects model using standardized mean differences (SMD) revealed a significant pooled effect (SMD = -0.24, p = 0.005). Subgroup and moderator analyses showed that adolescents exhibited greater improvements in CoD performance compared to adults (SMD = -0.42, p < 0.01), and elite athletes demonstrated larger gains compared to recreational active individuals (SMD = -0.43, p < 0.01). Among training modalities, resisted linear sprinting demonstrated consistent CoD benefits (SMD = -0.29, p < 0.01). Additionally, low-frequency training (SMD = -0.32), relative load (SMD = -0.22), and auto-regulated load (SMD = -0.53) were associated with enhanced CoD speed (all p < 0.05). These findings suggest that resisted training significantly improves CoD ability, particularly among adolescents and elite athletes. Optimizing training parameters, including load prescription, frequency, and resistive type, may effectively enhance CoD outcomes.